Expression for the first part is 2(x - 3) = x + 4, and for the second part is 3x = 2(x - 1).
It is defined as the combination of constants and variables with mathematical operators.
It is given that:
3. Twice the difference of a number and three is the sum of that number and four.
Mathematically,
The expression can be written as:
Let the number is x:
2(x - 3) = x + 4
4. Three times a number is two times the difference of that number and one:
The expression can be written as:
Let the number is y:
3x = 2(x - 1)
The expression for the first part is 2(x - 3) = x + 4, and for the second part is 3x = 2(x - 1).
Learn more about the expression here:
brainly.com/question/14083225
#SPJ1